Impact of Meteorological Parameters on Global Solar Radiation (GSR) at Nepalgunj Airport, Nepal - Gautam, Dilip; Neupane, Bijay Raj; Khadka, Narendra; Koirala, Maha Prasad; Baniya, Smriti; Baniya, Hom Bahadur (Amrit Journal, 2024)
Global solar radiation (GSR), is the main source of heat that powers the energy between the geosphere and the atmosphere, is the total of the direct and diffused shortwave solar radiation that reaches the earth’s surface. The target of the present report is to analyze the GSR from the data of Nepalgunj airport, Nepal in 2020. In addition, to analyze the effect of rainfall, relative humidity, maximum temperature, and minimum temperature to the GSR. The data on a horizontal surface for Nepalgunj airport, Nepal in 2020 were collected from the Department of Hydrology and Meteorology, Government of Nepal. The Angstrom-Prescott, Tiwari, and Sangeeta models were used to calculate the GSR theoretically on a horizontal surface with the help of the estimated sunshine hour. The yearly average value of GSR for the year 2020 was 18.73 MJ/m2/day. The measured GSR on a horizontal surface was found maximum in April which was 27.64 MJ/m2/day and minimum in August which was 6.38 MJ/m2/day The minimum amount of GSR found in August may be due to the high amount of rainfall of 10.51 mm in August. Talking about the seasonal variation, the Spring season receives the maximum amount of GSR i.e. 24.75 MJ/m2/day and the minimum amount is in winter i.e. 9.13 MJ/m2/day. Here, the summer season belongs to June, July, and August, and the minimum amount of solar radiation was found in August. During that month a high amount of rainfall was observed, and minimum amount of average temperature was observed. On studying the graph of variation of GSR with various meteorological parameters well-accepted relations were found. A direct relation is found between GSR and average maximum temperature, minimum temperature, rainfall, and relative humidity.